1962
DOI: 10.5962/bhl.title.10203
|View full text |Cite
|
Sign up to set email alerts
|

Whales / Translated by A.J. Pomerans.

Abstract: covered with scaleswhich is not at all surprising when we consider that it was not until the eighteenth century that dolphins were first distinguished from fishes, and this despite the fact that Aristotle, the father of biology and medicine, had pointed out as early as 400 b.c. that dolphins have warm blood and lungs, that they are viviparous, and that they suckle their young just as lun-ses, dogs and human beings do. Aristotle also mentioned the 'Mysticetus\ an animal which had 'pig's bristles' for teeth. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
37
0
1

Year Published

1981
1981
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(40 citation statements)
references
References 8 publications
(9 reference statements)
2
37
0
1
Order By: Relevance
“…Meek (1918) and Morejohn and Baltz (1972) observed that cetaceans belong to the few mammal groups (including Orders Artiodactyla, Perissodactyla and some species of insectivores such as bats) having vaginal folds. For Slijper (1962), while the outer part of the vagina is smooth with some longitudinal folds, the inner part has a larger number of prominent annular folds, which is similar to a chain funnel with the opening facing the uterine cervix. These features were also found in our study and it is suggested that these folds serve as a barrier to water during swimming and provide extra space to the birth canal, allowing it to extend during birth.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Meek (1918) and Morejohn and Baltz (1972) observed that cetaceans belong to the few mammal groups (including Orders Artiodactyla, Perissodactyla and some species of insectivores such as bats) having vaginal folds. For Slijper (1962), while the outer part of the vagina is smooth with some longitudinal folds, the inner part has a larger number of prominent annular folds, which is similar to a chain funnel with the opening facing the uterine cervix. These features were also found in our study and it is suggested that these folds serve as a barrier to water during swimming and provide extra space to the birth canal, allowing it to extend during birth.…”
Section: Discussionmentioning
confidence: 99%
“…Slijper (1962) stated that when the follicle matures it becomes distended by the accumulation of fluid within the antrum and moves out of the ovary surface.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Por otra parte, el haber encontrado en Bahía Málaga un ballenato de a lo sumo tres meses de edad con epibiontes jóvenes, adheridos en la parte ventral de la mandíbula inferior, indica que el ballenato adquirió los epibiontes en Colombia, muy posiblemente en Bahía Málaga. Este resultado confirma que los balanos se pueden adherir a las ballenas en aguas tropicales, tal como lo afirman Clarke (1966), Slijper (1979) y Félix et al (2006, y que además, estos epibiontes se establecen y permanecen tanto en ballenas adultas como en ballenatos de corta edad.…”
Section: Figunclassified
“…In most of the mysticete cetaceans, however, the pelvic bones are crescent-shaped and consisted of three parts [5]. The pelvic bones do not have bony articulations with the vertebral column in any of the cetacean species and they lack the appendicular skeleton except in some great whales such as Balaenidae, Balaenopteridae and Physeteridae that occasionally or usually have rudimentary femur or even tibia [3,15,16,23]. There are several works on the structures relating to the rudimentary pelvic bones in narwhal (Monodon monoceros) [13], pygmy sperm whale (Kogia breviceps) [21], and horbour porpoise (Phocoena phocoena) [22], but they gave no discussion on their evolutional nor functional significances.…”
mentioning
confidence: 99%